Integrative analysis of intestinal flora and untargeted metabolomics in attention-deficit/hyperactivity disorder - Jiamin Lu; Maoying Jiang; Dingyue Chai; Yuzi Sun; Lihui Wu (Frontiers in Microbiology)
Attention Deficit Hyperactivity Disorder (ADHD) is a clinically common neurodevelopmental disorder of the brain. In addition to genetic factors, an imbalance in gut flora may also play a role in the development of ADHD. Currently, it is critical to investigate the function of gut flora and related metabolites, which may form the fundamental basis of bidirectional cross-linking between the brain and the gut, in addition to focusing on the changed gut flora in ADHD. This study aimed to investigate the possible relationship between changes in gut flora and metabolites and ADHD by analyzing metagenome and untargeted metabolomics of fecal samples from ADHD patients. Specifically, we attempted to identify key metabolites and the metabolic pathways they are involved in, as well as analyze in detail the structure and composition of the gut flora of ADHD patients. In order to further investigate the relationship between gut flora and ADHD symptoms, some behavioral studies were conducted following the transplantation of gut flora from ADHD patients into rats. The results of the metagenome analysis revealed several distinct strains, including Bacteroides cellulosilyticus, which could be important for diagnosing ADHD. Additionally, the ADHD group showed modifications in several metabolic pathways and metabolites, including the nicotinamide and nicotinic acid metabolic pathways and the metabolite nicotinamide in this pathway. The behavioral results demonstrated that rats with ADHD gut flora transplants displayed increased locomotor activity and interest, indicating that the onset of behaviors such as ADHD could be facilitated by the flora associated with ADHD. This research verified the alterations in gut flora and metabolism observed in ADHD patients and provided a list of metabolites and flora that were significantly altered in ADHD. Simultaneously, our findings revealed that modifications to the microbiome could potentially trigger behavioral changes in animals, providing an experimental basis for comprehending the function and influence of gut flora on ADHD. These results might provide new perspectives for the development of novel treatment strategies.